2015
DOI: 10.1016/j.bpj.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

ATP Consumption of Eukaryotic Flagella Measured at a Single-Cell Level

Abstract: The motility of cilia and flagella is driven by thousands of dynein motors that hydrolyze adenosine triphosphate (ATP). Despite decades of genetic, biochemical, structural, and biophysical studies, some aspects of ciliary motility remain elusive, such as the regulation of beating patterns and the energetic efficiency of these nanomachines. In this study, we introduce an experimental method to measure ATP consumption of actively beating axonemes on a single-cell level. We encapsulated individual sea urchin sper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 58 publications
6
60
2
Order By: Relevance
“…In our theory, we assume an active flagellar driving force that is independent of external load. This assumption is consistent with recent experiments, which show that flagellar ATP consumption is rather insensitive to beat frequency and mechanical load [39]. Accordingly, any increase in load is compensated by a reduction in speed, not an increase in fuel consumption.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…In our theory, we assume an active flagellar driving force that is independent of external load. This assumption is consistent with recent experiments, which show that flagellar ATP consumption is rather insensitive to beat frequency and mechanical load [39]. Accordingly, any increase in load is compensated by a reduction in speed, not an increase in fuel consumption.…”
supporting
confidence: 81%
“…Previous estimates for η reported values in the range η = 0.1 − 0.4 [36][37][38][39], see also SM. In our theory, we assume an active flagellar driving force that is independent of external load.…”
mentioning
confidence: 99%
“…The consequent determination of gains, losses and modifications of sperm (or sperm‐associated seminal or female) proteins will provide molecular precision to our understanding of the sequence of changes in sperm as they reside in the FRT. Combining this approach with cryo‐electron‐tomography (Nicastro, McIntosh, & Baumeister, ) to reveal structural changes in the sperm and in the positions or shapes of complexes on or in them, and methods for single‐cell measurement of energy consumption (Chen et al ., ) in sperm will further extend the molecular precision of what is involved in PEMS. This in turn will provide a foundation for systematic efforts to examine the in vivo functional importance of PEMS, in organisms where genetic manipulation is possible, and establish molecular networks governing post‐copulatory sperm–female interactions critical to sperm viability and fertility (McDonough et al ., ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Further, using a hydrodynamic power balance, we were able to infer from the speed the corresponding diurnal variation in mean beat frequency. A study of demembraned Lytechinus pictus sea urchin sperm flagella has demonstrated ATP concentration correlates positively with flagellar beat frequency (34). We can reasonably hypothesise that a similar correlation will apply qualitatively for C. reinhardtii.…”
Section: Discussionmentioning
confidence: 55%
“…In particular, our data would suggest that during the dark period the amount of ATP available to flagella drops in value to a lower level that is maintained during the day; flagellar ATP then surges at the onset of division. To test if the flagellar frequency does indeed chart the variation of flagellar ATP, it would be very interesting to carry out experiments similar to (34) assaying the diurnal variation of ATP in the flagella of C. reinhardtii.…”
Section: Discussionmentioning
confidence: 99%